2010
DOI: 10.1111/j.1541-0072.2010.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Policy Streams: Testing the Separation of Problems and Solutions in Subnational Policy Systems

Abstract: The multiple streams theory of national policymaking has been influential in the study of public administration and public policy-if not without a fair bit of controversy. While some laud the model for its openness to the important role of policy entrepreneurs and the irrationalities of the decisionmaking processes, others criticize the model for its lack of readily testable propositions. This article identifies a series of testable propositions in the multiple streams model (particularly that discussed by Kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 12 publications
(11 reference statements)
0
46
0
Order By: Relevance
“…This is difficult to ensure, given the ever-changing and ambiguous nature of reality (Robinson & Eller, 2010). However, the streams provide good analytical categories.…”
Section: The Limitations Of the Multiple Streams Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…This is difficult to ensure, given the ever-changing and ambiguous nature of reality (Robinson & Eller, 2010). However, the streams provide good analytical categories.…”
Section: The Limitations Of the Multiple Streams Frameworkmentioning
confidence: 99%
“…First, the fluid participation of government officials affects rationality and predictability. For instance, as Robinson and Eller (2010) explained, participants at any meeting may vary considerably, and different officials may devote different levels of energy to the decision-making process. In one case, the government had sent more than five officials to try to mediate with the government (SCMP, 2013), but all of these officials had different goals.…”
Section: The Multiple Streams Framework In the Context Of The Mne Curmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Travis and Zahariadis () made note of the lack of quantitative work being produced using multi‐streams model and our research found that the scenario has not changed since. Our search found only one another journal study (by Robinson and Eller ), which argued that Kingdon's model does provide falsifiable predictions, and that employed a quantitative model to test these predictions. Some other studies (see e.g., Kubiak, Sobek, and Rose ; Rios and Meyer ) used quantitative data along with qualitative data in their studies.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of United Nations peacekeeping as an example of garbage can policymaking, Lipson (2007) also found that arriving at solutions was a result of temporal sorting as opposed to rationally fitting solutions with policies. Robinson and Eller (2010) discuss the Multiple Streams garbage can model (Zahariadis 2007) which emphasizes that policy makers work under significant time constraints and that the streams feeding into policy (problems, solutions, politics) are often independent from one another. There tends to be significant ambiguity in garbage cans due to fluid participation, problematic preferences, and unclear technology (204).…”
Section: The Garbage-can Modelmentioning
confidence: 99%